2010
DOI: 10.1089/jmf.2009.0149
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Ingestion of Prehydrolyzed Whey Protein Induces Little or No Change in Digestive Enzymes, but Decreases Glutaminase Activity in Exercising Rats

Abstract: Because consumption of whey protein hydrolysates is on the increase, the possibility that prolonged ingestion of whey protein hydrolysates affect the digestive system of mammals has prompted us to evaluate the enzymatic activities of pepsin, leucine-aminopeptidase, chymotrypsin, trypsin, and glutaminase in male Wistar rats fed diets containing either a commercial whey isolate or a whey protein hydrolysate with medium degree of hydrolysis and to compare the results with those produced by physical training (sede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…The various advantages pointed out for the whey protein hydrolyzates are consistent also with a possible beneficial effect to the experimental animal, as has been the case of physical performance in rats undergoing endurance exercise (Morifuji et al, 2009;Pimenta et al, 2005) and promoting the synthesis of glycogen (Morifuji et al, 2009). Nery-Diez et al (2010 additionally have suggested an anti-stress effect associated with the consumption of the whey protein hydrolyzate in rats undergoing endurance exercise.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…The various advantages pointed out for the whey protein hydrolyzates are consistent also with a possible beneficial effect to the experimental animal, as has been the case of physical performance in rats undergoing endurance exercise (Morifuji et al, 2009;Pimenta et al, 2005) and promoting the synthesis of glycogen (Morifuji et al, 2009). Nery-Diez et al (2010 additionally have suggested an anti-stress effect associated with the consumption of the whey protein hydrolyzate in rats undergoing endurance exercise.…”
Section: Introductionsupporting
confidence: 56%
“…Hydrolyzing the protein alone could in itself alter the biological function of the protein, thus affecting metabolism (Meisel, 1998). It has been suggested, for instance, that the mere change of the physicochemical form in which the protein is presented to the animal suffices to influence the general metabolism, apparently as a result of the various peptides that are generated during partial enzymatic hydrolysis of the whey proteins (Morifuji et al, 2009;Nery-Diez et al, 2010;Faria et al, 2012). Alteration in glycogen metabolism has been perhaps the most often reported positive feature resulting from substituting a whey protein hydrolyzate for the native Grouping of animals by type of diet and physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous findings by the present [3], [7], [8] and other [10], [23] authors clearly showing that the consumption of WP and WPH raised muscle and hepatic glycogen levels, the objective of the present study was to verify the effect that the consumption of WP and WPH had on the translocation of the glucose transporters GLUT-4 and GLUT-1 to the plasma membrane (PM), as compared to rats fed a standard diet (AIN93-G) with casein as the protein source. The results showed clearly that the consumption of WP and WPH increased the translocation of GLUT-4 (Figure 2A) when compared to the casein-fed animals, whereas GLUT-1 (Figure 2B) was not responsive to the different proteins.…”
Section: Discussionmentioning
confidence: 61%
“…Different food proteins may affect muscle metabolism in different fashions, as shown when the effects of whey proteins (WP) are compared to those of casein (CAS) [1][3]. One difference between WP and CAS is that WP stimulates an increase of fatty acid synthesis in the muscle accompanied by a concomitant decrease in fatty acid synthesis in the liver, considered to be a positive effect on lipid metabolism [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation